Implementation of Learning Cycle to Improve Electrochemistry Learning Outcomes for 10th Graders of Vocational High Schools - Nelli Purba; Hartono Hartono; Rahman Susanto (Research in Education, Technology, and Multiculture, 2022)
Abstract: Improving Student Chemistry Learning Outcomes through Learning Cycle Models in SMK. This research aims to determine whether Learning Cycle can improve students' chemistry learning outcomes in class X SMK Negeri 4 Palembang. This Research use Subject at students of class X TKR 1 SMK Negeri 4 Palembang, amounting to 30 students. This research is a Classroom Action Research (PTK) which is implemented in two cycles. Data obtained from each cycle were analyzed to determine the development of learning and as a correction thing in the next cycle. Data collection is done through an evaluation test at the end of each learning cycle. The collected data was analyzed statistically using class average and percent student's classical. In the first cycle the average score of students is 63.67 and the percentage of students' classical is 43.33%. While in the second cycle there is an increase in student learning that can be seen from the average score of students by 82 and percent classical student to 86.67%. Therefore, the application of Leaning Cycle learning model in chemistry learning, especially electrochemical learning can improve student learning outcomes. Keywords: learning cycle, learning outcomes, electrochemistry, classroom action research.